Peranan Sistem Informasi Manajemen terhadap Efektivitas dan Gaya Kepemimpinan di Era Digital - Rosit Dwi Atmaja; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the role of Management Information Systems in leadership effectiveness and style in the digital era. The development of information technology has driven significant changes in how leaders manage organizations, make decisions, and interact with subordinates. Information systems serve as the main tool for providing fast, accurate, and relevant data to support managerial processes and improve organizational efficiency. The implementation of integrated systems helps leaders build leadership styles that are more adaptive, participatory, and based on digital collaboration. Effective use of information also enhances transparency, communication, and work productivity. Therefore, the integration between management information systems and modern leadership styles is an essential factor in creating resilient, innovative, and competitive organizations in today’s digital challenges.